2020
DOI: 10.1186/s13046-020-01734-4
|View full text |Cite
|
Sign up to set email alerts
|

UBE2T-regulated H2AX monoubiquitination induces hepatocellular carcinoma radioresistance by facilitating CHK1 activation

Abstract: Background Radioresistance is the major obstacle in radiation therapy (RT) for hepatocellular carcinoma (HCC). Dysregulation of DNA damage response (DDR), which includes DNA repair and cell cycle checkpoints activation, leads to radioresistance and limits radiotherapy efficacy in HCC patients. However, the underlying mechanism have not been clearly understood. Methods We obtained 7 pairs of HCC tissues and corresponding non-tumor tissues, and UBE2T was identified as one of the most upregulated genes. The rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 41 publications
2
45
0
Order By: Relevance
“…Additionally, the cell cycle checkpoint is verified to be one of the most important cell cycle regulatory mechanisms [ 56 ]. Nonetheless, dysregulation of the cell cycle checkpoint might lead to radio resistance of HCC cells, thus causing unfavourable prognosis in HCC patients [ 57 ]. Therefore, the upregulated LPCAT1 CEGs might induce abnormal regulation of the cell cycle and promote the development and deterioration of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cell cycle checkpoint is verified to be one of the most important cell cycle regulatory mechanisms [ 56 ]. Nonetheless, dysregulation of the cell cycle checkpoint might lead to radio resistance of HCC cells, thus causing unfavourable prognosis in HCC patients [ 57 ]. Therefore, the upregulated LPCAT1 CEGs might induce abnormal regulation of the cell cycle and promote the development and deterioration of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in nding useful biomarkers for diagnosis and treatment of breast cancer has been accumulating. Increasing data indicated that aberrant UBE2T expression has serve important roles in almost all cell biological behaviors, including growth, cell cycle, apoptosis, differentiation, apoptosis and metastasis (14)(15)(16)(17). However, little is known about the function of UBE2T in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…NEDD4L triggers the degradation of certain proteins involved in cancer progression, most of which attributed to its E3 ubiquitin ligase function [16,20,35]. Meanwhile, overexpression of UBE2T has been found in a variety type of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, UBE2T could promote gastric cancer cell progression via hyperactivating the Wnt/β-catenin pathway through the ubiquitination and degradation of RACK1 [16]. On the other hand, UBE2T also could mediate H2AX/γH2AX monoubiquitylation on facilitating cell cycle arrest activation to provide su cient time for radiationinduced DNA repair, thus conferring hepatocellular carcinoma radio-resistance [20]. Consistently, UBE2T was overexpressed and associated with poor prognosis in gastric cancer [16], hepatocellular carcinoma [20], osteosarcoma [17] and breast cancer [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation